ANALYSIS OF PUBLIC ACCOUNTING INFORMATION SYSTEM AT THE DEVELOPMENT PLANNING AGENCY OF NORTH SUMATRA - Rasmita Tiara Br Barus; Kamilah K (Jurnal RAK (Riset Akuntansi Keuangan), 2022)
SKPD is an entity that uses an accounting system such as in a company, but this SKP focuses on regional units under the leadership of the government. BAPPEDA is one of the Regional Apparatus Work Units. The benefits that can be taken from this research is to analyze how the government accounting information system exists at the Regional Planning and Development Agency (BAPPEDA) in the province of North Sumatra, whether it has used the laws and regulations that have been set in the Ministry of Home Affairs No. 2020 and whether they have used an information system regarding standard accounting or not. The ideas used in this research are the regional accounting data framework, the investigation of the regional accounting data framework, and the examination of unofficial laws used in monetary announcement readiness. The research shows that the implementation of the accounting information system at the Regional Development Planning Agency in North Sumatra has complied with government regulations that serve as guidelines in the preparation of financial reporting contained in the Ministry of Home Affairs Number 77 of 2020.